Fabricating an Accurate Implant Master Cast: A Technique Report. Issue 8 (27th July 2015) - Balshi, Thomas J.; Wolfinger, Glenn J.; Alfano, Stephen G.; Cacovean, Jeannine N.; Balshi, Stephen F.
Abstract: The technique for fabricating an accurate implant master cast following the 12‐week healing period after Teeth in a Day® dental implant surgery is detailed. The clinical, functional, and esthetic details captured during the final master impression are vital to creating an accurate master cast. This technique uses the properties of the all‐acrylic resin interim prosthesis to capture these details. This impression captures the relationship between the remodeled soft tissue and the interim prosthesis. This provides the laboratory technician with an accurate orientation of the implant replicas in the master cast with which a passive fitting restoration can be fabricated.